Case of a Pharyngeal Foreign Body with Cutaneous Migration, Resembling a Fishbone, Observed in the Ent Department of the Mamou Regional Hospital, Guinea - Diallo, Mamadou Mouctar Ramata; Diallo, Mamadou Aliou; Diallo, Ibrahima; Diallo, Oumou Amadou; Sow, Abdoulaye; Cissé, Alsény; Sacko, Sory; Camara, Alsény; Kourouma, Sayon; Diallo, Alpha Oumar; Keita, Abdoulaye; Barry, Mamadou Sakoba (Medical Research and Its Applications Vol. 3, 2024)
The study presents a case of a 24-year-old rural resident, in whom a pharyngeal foreign body migrated through the skin in the form of a fishbone. He presented with odynophagia, dysphagia, pain, and a left anterolateral cervical swelling fistulized to the skin, following ingestion of a fishbone two weeks prior. Vital signs were stable, and psychological examination was normal. Clinical examination revealed a painful left anterolateral cervical swelling palpable on examination, with a cutaneous fistula and frank pus discharge, confirming the presence of a sharp fishbone. Standard radiography showed the foreign body had exited the pharynx and was located in the soft tissues of the lower neck. An exploratory cervicotomy was performed, allowing extraction of the serrated fishbone. The patient recovered well postoperatively. The delay in the correct management of this patient, who presented with a foreign body initially incarcerated in the hypopharynx, was due to insufficient interdisciplinary collaboration and the important role played by traditional medicine in our context. The multiple manipulations favored extra pharyngeal migration of the fishbone towards the cervical region.